Nurse’s life world in organ donation and tissue - Karine de Melo Cezar Alves; Isabel Comassetto; Guilherme Oliveira de Albuquerque Malta; Regina Maria dos Santos; Gian Carlos Rodrigues do Nascimento; Igor Michel Ramos dos Santos (Revista Brasileira de Enfermagem)
ABSTRACT Objectives: to understand the experience of nurses immersed in the everyday world of organ and tissue donation. Methods: study on the social phenomenology of Alfred Schütz, carried out with 27 nurses who work on Intra-Hospital Committees for Donation of Organs and Tissues for Transplants in states in the Northeast of Brazil. Data were collected through phenomenological interviews and analyzed according to the adopted framework and compared with scientific productions. Results: the nurses’ experiences allowed us to glimpse the achievement and remaining immersed in the space of the world of daily life of organ and tissue donation. Final Considerations: the experience of nurses from different actions in the lives of people who depend on an organ and tissue transplant concerns the social relations established in the world of life.